The cliffs eaudiobook - Sullivan, J. Courtney (Books on Tape, 2024)
REESE'S BOOK CLUB PICK • A novel of family, secrets, ghosts, and homecoming set on the seaside cliffs of Maine, by the New York Times best-selling author of Friends and Strangers “A stunning achievement, and J. Courtney Sullivan’s best book yet. Sullivan weaves a narrative that’s fascinating and thought-provoking. I literally could not put this book down.” —Ann Napolitano, New York Times best-selling author of Hello Beautiful On a secluded bluff overlooking the ocean sits a Victorian house, lavender with gingerbread trim, a home that contains a century’s worth of secrets. By the time Jane Flanagan discovers the house as a teenager, it has long been abandoned. The place is an irresistible mystery to Jane. There are still clothes in the closets, marbles rolling across the floors, and dishes in the cupboards, even though no one has set foot there in decades. The house becomes a hideaway for Jane, a place to escape her volatile mother. Twenty years later, now a Harvard archivist, she returns home to Maine following a terrible mistake that threatens both her career and her marriage. Jane is horrified to find the Victorian is now barely recognizable. The new owner, Genevieve, a summer person from Beacon Hill, has gutted it, transforming the house into a glossy white monstrosity straight out of a shelter magazine. Strangely, Genevieve is convinced that the house is haunted—perhaps the product of something troubling Genevieve herself has done. She hires Jane to research the history of the place and the women who lived there. The story Jane uncovers—of lovers lost at sea, romantic longing, shattering loss, artistic awakening, historical artifacts stolen and sold, and the long shadow of colonialism—is even older than Maine itself. Enthralling, richly imagined, filled with psychic mediums and charlatans, spirits and past lives, mothers, marriage, and the legacy of alcoholism, this is a deeply moving novel about the land we inhabit, the women who came before us, and the ways in which none of us will ever truly leave this earth.